(untitled) (Bioremediation Science and Technology Research (e-ISSN 2289-5892), 2022)
The anionic surfactant known as sodium dodecyl sulfate (SDS) or sodium lauryl sulfate (SLS) is found in a wide variety of products designed for cleaning and personal hygiene. Because of the combination of its hydrocarbon tail and its polar "headgroup," the molecule possesses the amphiphilic qualities that make it suitable for use as a detergent. Due to this it is a major pollutant in aquatic bodies. One of the most researched types of cleanup is biodegradation by microorganisms, particularly bacteria. Copper has a profound effect in inhibiting the degradation of SDS by the bacteria Serratia marcescens strain DRY6. Under different copper concentrations, the SDS-degrading bacteria grew in a sigmoidal manner with lag times of 7 to 10 hours. Overall growth was decreased when the concentration of copper was raised, with 1.0 g/L virtually completely stopping bacterial growth. Rates of expansion at various copper concentrations were calculated using a modified Gompertz model. Following the modification of the Gompertz model, the growth rates were modeled using the modified Han-Levenspiel, Wang, Liu, modified Andrews, and the Amor models. Only three of the five models (Wang, modified Han-Levenspiel, and the Liu models) were able to match the curve; the modified Andrews and Amor models did not. As for model fit, the Wang and modified Han-Levenspiel models perform admirably, but the Liu model performs poorly. The Wang model performed best statistically, with the lowest RMSE and AICc values, the greatest adjusted correlation coefficient (adR2), and AF and BF values closest to unity. The Wang model yielded estimates of 0.216 (95% confidence interval: 0.193 to 0.239), 1.05 (95% confidence interval: 0.938 to 1.167), and 0.389 (95% confidence interval: 0.148 to 0.636) for the critical heavy metal ion concentration (g/l), maximum growth rate (g/l h), and empirical constant.